2020
DOI: 10.3390/nano10050967
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Engineered Silver Nanomaterials on the Immune System

Abstract: Over the last decades there has been a tremendous volume of research efforts focused on engineering silver-based (nano)materials. The interest in silver has been mostly driven by the element capacity to kill pathogenic bacteria. In this context, the main area of application has been medical devices that are at significant risk of becoming colonized by bacteria and subsequently infected. However, silver nanomaterials have been incorporated in a number of other commercial products which may or may not benefit fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 205 publications
0
38
0
Order By: Relevance
“…93 Several researchers reported the impact of AgNMs on the inflammatory response. 94 Silver was reported to react with immune cells and affect the suppression or stimulation of various pathological conditions. It was reported that an increase in the size of AgNMs resulted in an increase in inflammatory cytokine secretion in rat alveolar macrophages, 95 toxicological effects on macrophage U937, 96 and also elicited an immune response in macrophages.…”
Section: Agnms As Vaccinesmentioning
confidence: 99%
“…93 Several researchers reported the impact of AgNMs on the inflammatory response. 94 Silver was reported to react with immune cells and affect the suppression or stimulation of various pathological conditions. It was reported that an increase in the size of AgNMs resulted in an increase in inflammatory cytokine secretion in rat alveolar macrophages, 95 toxicological effects on macrophage U937, 96 and also elicited an immune response in macrophages.…”
Section: Agnms As Vaccinesmentioning
confidence: 99%
“…AgNPs also trigger inflammatory reactions cascade involving the activation of macrophages, neutrophils, and helper T cells [ 155 ]. Subsequently, AgNPs enhance the expression of numerous types of cytokines [ 156 , 157 ].…”
Section: Nanoparticles and Nanoparticles-based Drug Delivery Systementioning
confidence: 99%
“…The engineering of silver-based nanomaterials (NMs) has experienced a tremendous technological evolution in the last decade. Although antibacterial activity of silver has been well known since the development of medicine in ancient civilizations, its inclusion in nanostructures has allowed increased biocompatibility and development of more efficient nanoproducts for biomedicine [1]. Thus, silver nanoparticles (AgNPs) became one of the most investigated and exploited NMs due to their unique optical, electrical and biological properties [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous biomedical applications such as coatings for medical device and tissue regeneration materials, AgNPs awoke tremendous interest in therapeutic applications including drug or vaccine delivery platforms. Emerging problem of drug resistance emphasized broad variety of AgNPs designs as promising alternatives [1,3]. However, interaction of AgNPs with the immune system remains a key enigma for their implementation in such therapeutic tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation